Konsep Pendidikan Informal Perspektif Ibnu Sahnun (Telaah Kitab Adab Al-Muallimin) - Anisatun Nur Laili (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2020)
The family is the holder of control in informal education, especially in shaping the religious character of children from an early age. The intellectual, social, and emotional development of children is very fast in the golden age so that parents as holders of an important role in children's development must have the readiness and knowledge that is qualified for the successful implementation of informal education. This research is a library research that focuses on examining the thoughts of Ibn Sahnun, a scholar in the field of education in the 2nd century H. Related to the concept of informal education which he wrote in the book of Adab al-Mu'allimin. According to Ibnu Sahnun the main curriculum in informal education is the education of the Qur'an so that it is integrated with the general knowledge acquired by children in formal education. The obligation to educate is absolutely the property of parents, in addition to preparing knowledge, parents must also form noble qualities in themselves as educators, including patience, sincerity, fairness, responsibility, and gentle in educating. However, if parents really are not able to educate their children, then they are obliged to find a teacher for their children and give a salary to the teacher, but still supervise and accompany their children